2003
DOI: 10.1590/s0034-89102003000400006
|View full text |Cite
|
Sign up to set email alerts
|

Aspectos psicossociais do trabalho e distúrbios psíquicos entre trabalhadoras de enfermagem

Abstract: OBJETIVO: Avaliar a associação entre demanda psicológica e controle sobre o trabalho e a ocorrência de distúrbios psíquicos menores entre trabalhadoras de enfermagem. MÉTODOS: Estudo de corte transversal, incluindo 502 trabalhadoras de enfermagem de um hospital público de Salvador, Bahia. O Modelo Demanda-Controle, de Karasek, foi utilizado para avaliar as dimensões psicossociais estudadas. Para mensuração de distúrbios psíquicos menores (DPM), utilizou-se o SRQ-20. RESULTADOS: A prevalência de DPM foi 33,3%, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
74
3
131

Year Published

2006
2006
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 163 publications
(232 citation statements)
references
References 16 publications
13
74
3
131
Order By: Relevance
“…22,f The percentage of 39.6% of positive CAGE (alcohol abuse) was greater than that found in studies performed with other populations in Salvador. 1,3 This high percentage could be associated with cultural work aspects in this population that need to be further analyzed.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…22,f The percentage of 39.6% of positive CAGE (alcohol abuse) was greater than that found in studies performed with other populations in Salvador. 1,3 This high percentage could be associated with cultural work aspects in this population that need to be further analyzed.…”
Section: Discussionmentioning
confidence: 97%
“…3,26 Prevalence of CMDs among electrical workers in the metropolitan area of Vitória, Southeastern Brazil, was 18.7%. a Another study with electrical workers, which used different instruments and methods, also showed changes in the mental health of such workers.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations